Learning Management At Majelis Taklim Al-Huda - Sayuti, Muhamad Deden Jalaludin; Widara, Yuyun; Iqbal, Muhammad; Lestari, Dwi Endah (J-MPI (Jurnal Manajemen Pendidikan Islam), 2024)
The purpose of this research is to find out the learning management of Majelis Taklim Al Huda Mundu Cirebon Regency. The method used in this research is a qualitative method. Information was collected through observation, interviews and document studies. The results showed that the leader of the taklim assembly determines the plan by compiling a curriculum, identifying the books to be studied by adjusting the needs of the students, starting from the statute to the continuation. In its implementation, there are 3 age categories in the learning process at Majelis Taklim Al Huda, including children, teenagers / adults and parents. The teachers deliver the material with various methods such as bandongan, sorogan, memorization, and lectures. As for the recitation of parents, it is carried out with lecture and question and answer methods. The evaluation stage is carried out where children and teenage students are asked to explain back the lessons that have been learned previously. In addition, through memorization the student deposits the memorized memorization. The evaluation is carried out every day before and after the learning process. However, the learning evaluation does not apply to parent category learning. This is because the target of majelis taklim for parents is intended for knowledge and education about Islam.